Impact of fluid balance and opioid-sparing anesthesia within enchanced recovery pathway on postoperative morbidity after transthoracic esophagectomy for cancer - Djukanovic, Marija; Skrobic, Ognjan; Stojakov, Dejan; Knezevic, Nebojsa Nick; Milicic, Biljana; Sabljak, Predrag; Simic, Aleksandar; Milenkovic, Marija; Sreckovic, Svetlana; Markovic, Dejan; Palibrk, Ivan (Frontiers in Medicine, 2024)
Background: Enhanced Recovery After Surgery (ERAS) protocol for esophagectomy may reduce the high incidence of postoperative morbidity and mortality. The aim of this study was to assess the impact of properly conducted ERAS protocol with specific emphasis on fluid balance and opioid-sparing anesthesia (OSA) on postoperative major morbidity and mortality after esophagectomy.Methods: Patients undergoing elective esophagectomy for esophageal cancer at the Hospital for Digestive Surgery, University Clinical Center of Serbia, from December 2017 to March 2021, were included in this retrospective observational study. Patients were divided into two groups: the ERAS group (OSA, intraoperative goal-directed therapy, and postoperative "near-zero" fluid balance) and the control group (opioid-based anesthesia, maintenance mean blood pressure ≥65mmHg, and liberal postoperative fluid management). The primary outcome was major morbidity within 30 days from surgery and 30-day and 90-day mortality. Multivariable analysis was used to examine the effect of the ERAS protocol.Results: A total of 121 patients were divided into the ERAS group (69 patients) and the control group (52 patients). Patients in the ERAS group was received less fentanyl, median 300 (interquartile range (IQR), 200-1550) mcg than in control group, median 1100 (IQR, 650-1750) mcg, p<0.001. Median intraoperative total infusion was lower in the ERAS group, 2000 (IQR, 1000-3750) ml compared to control group, 3500 (IQR, 2000-5500) ml, p<0.001. However, intraoperative norepinephrine infusion was more administered in the ERAS group (52.2% vs. 7.7%, p<0.001). On postoperative day 1, median cumulative fluid balance was 2215 (IQR, -150-5880) ml in the ERAS group vs. 4692.5 (IQR, 1770-10060) ml in the control group, p=0.002.After the implementation of the ERAS protocol, major morbidity was less frequent in the ERAS group than in the control group (18.8% vs. 75%, p<0.001). There was no statistical significant difference in 30-day and 90-day mortality (p=0.07 and p=0.119, respectively). The probability of postoperative major morbidity and interstitial pulmonary edema were higher in control group (OR 5.637; p=0.030 and OR 5.955; CI95% 1.702-9.084; p <0.001, respectively). Conclusion: A major morbidity and interstitial pulmonary edema after esophagectomy were decreased after the implementation of the ERAS protocol, without impact on overall mortality.